2020
DOI: 10.1016/j.heares.2020.108000
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection causes widespread damage to the inner ear

Abstract: Zika virus (ZIKV) has been recently recognized as a causative agent of newborn microcephaly, as well as other neurological consequences. A less well recognized comorbidity of prenatal ZIKV infection is hearing loss, but cases of hearing impairment following adult ZIKV infection have also been recognized. Diminished hearing following prenatal ZIKV infection in a mouse model has been reported, but no cellular consequences were observed. We examined the effects of ZIKV infection on inner ear cellular integrity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 103 publications
0
12
0
1
Order By: Relevance
“…The susceptibility of the inner ear tissues to ZIKV was recently reported for two vertebrate animal models: chicken embryos [9] and adult mice with compromised immune systems [10]. In the chicken embryo, our group found that the inner ear could be infected by direct delivery of virus into the fluid compartment of the inner ear.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The susceptibility of the inner ear tissues to ZIKV was recently reported for two vertebrate animal models: chicken embryos [9] and adult mice with compromised immune systems [10]. In the chicken embryo, our group found that the inner ear could be infected by direct delivery of virus into the fluid compartment of the inner ear.…”
Section: Introductionmentioning
confidence: 71%
“…This suggests that the different inner ear cell types may have specific critical periods of susceptibility and sensitivity to ZIKV, although until now this has not been tested in an embryonic mammalian inner ear. In the 5−6-week-old immunocompromised mouse, systemic ZIKV delivery resulted in infection of the inner ears as well as subsequent histological pathologies at 9 days post-infection [10]. Cellular damage (swelling, intracellular vacuoles, translocation of the nucleus and/or apical surface blebbing) was observed in the sensory epithelia (both auditory and vestibular) or in the spiral ganglion, whose axons bundle to form the auditory nerve.…”
Section: Introductionmentioning
confidence: 99%
“…A bioinformatics and in vitro study showed the activation of a proliferative and pro-apoptotic P-53 related response in human neural progenitor cells in response to ZIKV ( Ghouzzi et al, 2016 ). Infection in adult mice revealed the presence of vacuolization in the stria vascularis, the dark cells of the vestibule, and the spiral ganglion ( Yee, Neupane, Bai, & Vetter, 2020 ). In utero infection of mice led to hearing deficits in 25% to 66% of the offspring, with a greater deficit at higher frequencies ( Julander et al, 2018 ).…”
Section: Environmental Causes Of Congenital Hearing Lossmentioning
confidence: 99%
“…A relation between Zika virus infection and hearing loss was also reported in both infants and adults. Zika virus was found to produce a graded distribution of cellular damage in the cochlea, with the greatest damage in the apex, in a manner similar to cytomegalovirus infection [ 32 , 40 , 41 ].…”
Section: Inner Ear Infectionsmentioning
confidence: 99%